(untitled) (Kinesiology, 2020)
The aims were to assess differentiated perceived match exertion and its variability according to playing position for professional soccer players. Nineteen Spanish players declared their respiratory and muscular perceived exertions after official matches during an entire season. Players were classified according to their playing position. In order to assess differentiated perceived match exertion, soccer players were asked to assess their perceived level of exertion following each official match. Considerable differences (p<0.05; ES = 0.41-2.49) were found between some playing positions. Furthermore, match-to-match differentiated perceived match exertion variability ranged from 12.8 to 27.7% for respiratory perceived exertion and from 11.5 to 25.2% for muscular perceived exertion according to playing position. Match respiratory-muscular perceived exertion differences varied among the playing positions, showing higher muscular perceived exertion than respiratory perceived exertion in central backs, wide midfielders and central midfielders (p<0.05; ES =-0.35 to 0.68), but higher respiratory perceived exertion than muscular perceived exertion in wing backs (p<0.05; ES =-0.35). Soccer match is different inter and intra some playing positions, showing large swings for match-to-match variability between playing positions. These facts confirm that the deconstruction of the overall perceived exertion provides a more accurate evaluation of the subjective match internal load in some playing positions.